Adaptive optimization by 6 DOF robotic couch in prostate volumetric IMRT treatment: rototranslational shift and dosimetric consequences. (8th September 2015) - Chiesa, Silvia; Placidi, Lorenzo; Azario, Luigi; Mattiucci, Gian Carlo; Greco, Francesca; Damiani, Andrea; Mantini, Giovanna; Frascino, Vincenzo; Piermattei, Angelo; Valentini, Vincenzo; Balducci, Mario
Abstract : The purpose of this study was to investigate the magnitude and dosimetric relevance of translational and rotational shifts on IGRT prostate volumetric‐modulated arc therapy (VMAT) using Protura six degrees of freedom (DOF) Robotic Patient Positioning System. Patients with cT3aN0M0 prostate cancer, treated with VMAT simultaneous integrated boost (VMAT‐SIB), were enrolled. PTV2 was obtained adding 0.7 cm margin to seminal vesicles base (CTV2), while PTV1 adding to prostate (CTV1) 0.7 cm margin in all directions, except 1.2 cm, as caudal margin. A daily CBCT was acquired before dose delivery. The translational and rotational displacements were corrected through Protura Robotic Couch, collected and applied to the simulation CT to obtain a translated CT (tCT) and a rototranslated CT (rtCT) on which we recalculated the initial treatment plan (TP). We analyzed the correlation between dosimetric coverage, organs at risk (OAR) sparing, and translational or rotational displacements. The dosimetric impact of a rototranslational correction was calculated. From October 2012 to September 2013, a total of 263 CBCT scans from 12 patients were collected. Translational shifts were < 5 mm in 81% of patients and the rotational shifts were < 2 ∘ in 93% of patient scans. The dosimetric analysis was performed on 172 CBCT scans and calculating 344 VMAT‐TP. Two significant linear correlations were observed between yaw and the V20 femoral heads and between pitch rotation and V50 rectum ( p < 0.001 ); rototranslational correction seems to impact more on PTV2 than on PTV1, especially when margins are reduced. Rotational errors are of dosimetric significance in sparing OAR and in target coverage. This is relevant for femoral heads and rectum because of major distance from isocenter, and for seminal vesicles because of irregular shape. No correlation was observed between translational and rotational errors. A study considering the intrafractional error and the deformable registration is ongoing. PACS number: 87.55.de